Socioeconomic position and SARS-CoV-2 infections: seroepidemiological findings from a German nationwide dynamic cohort. Issue 4 (28th September 2021) - Hoebel, Jens; Grabka, Markus M; Schröder, Carsten; Haller, Sebastian; Neuhauser, Hannelore; Wachtler, Benjamin; Schaade, Lars; Liebig, Stefan; Hövener, Claudia; Zinn, Sabine
Abstract : Background: Evidence on the relationship between socioeconomic position (SEP) and infections with SARS-CoV-2 is still limited as most of the available studies are ecological in nature. This is the first German nationwide study to examine differences in the risk of SARS-CoV-2 infections according to SEP at the individual level. Methods: The 'CORONA-MONITORING bundesweit' (RKI-SOEP) study is a seroepidemiological survey among a dynamic cohort of the German adult population (n=15 122; October 2020–February 2021). Dried blood samples were tested for SARS-CoV-2 antibodies and oral-nasal swabs for viral RNA. SEP was measured by education and income. Robust logistic regression was used to examine adjusted associations of SARS-CoV-2 infections with SEP. Results: 288 participants were seropositive, PCR positive or self-reported a previous laboratory-confirmed SARS-CoV-2 infection. The adjusted odds of SARS-CoV-2 infection were 1.87-fold (95% CI 1.06 to 3.29) higher among low-educated than highly educated adults. Evidence was weaker for income differences in infections (OR=1.65; 95% CI 0.89 to 3.05). Highly educated adults had lower odds of undetected infection. Conclusion: The results indicate an increased risk of SARS-CoV-2 infection in low-educated groups. To promote health equity in the pandemic and beyond, social determinants should be addressed more in infection protection and pandemic planning.